Impact of various luting cements on the fixed dentures bonding strength - Krunić Nebojša; Tonić Goran (Vojnosanitetski Pregled)
Background/Aim. Various luting cements are used to fix dental crowns to prepared teeth, and should provide an adhesive bond to the tooth structure giving reliable retention. The aim of this study was to establish in vitro which type of the tested luting cement provided the strongest adhesive bond of the prepared teeth to the fixed denture. Methods. Testing was carried out on the sample of 100 intact human premolars extracted for orthodontic reasons. The preparation of the teeth was performed by a heavy-duty machine. The surfaces of the prepared teeth were mathematically calculated. Dental crowns from the Nickel-Chromium- Molybenum (Ni-Cr-Mo) alloy were made in a standard fashion, and fixed to prepared teeth (two samples of each group) with 5 different types of luting cements. The strength of force applyed to separate the cast crowns from the prepared teeth was measured by an electronic dynamometer, after 7 days. Results. The obtained results revealed the connection between the type of luting cement and the values of retention power. The best adhesive bond under the constant convergence angle of the prepared teeth was provided by the resin cement. Conclusion. When choosing a luting cement for fixing dental crowns to prepared teeth, the advantage should be given to the resin cement in case the glassionomers are not available.